Challenges and Issues in Environmental Studies (EVS) Teaching at the Primary Stage - Dogra, Bharti (INDIAN EDUCATIONAL REVIEW, 2013)
Environmental Studies (EVS) is an integrated course on sciences and social studies for classes III to V. NCF (2005) has recommended use of thematic approach for EVS teaching. The entire EVS syllabus is divided into six themes which are further divided into sub themes. Another highlight of present EVS syllabus is Social Constructivist Perspective of learning. The emphasis is to impart not only conceptual knowledge but also develop process skill in students. Why should we expect so much from EVS teachers when they themselves were never taught during their school days through investigatory approach or never prepared later to teach this new EVS syllabus? EVS teachers in such a case are unable to transact the curriculum in the right spirit. These important aspects of the EVS teaching-learning become big challenges for them. This paper is an attempt to find out the challenges and issues faced by the EVS teachers and it also helps in formulating simple strategies to convert these challenges into opportunities.